Geração automática de código a partir da manipulação de modelos - Souza, Mariany Aparecida de (2017)
This work is based on the process of integrating a modeling tool that uses states machines or Automata, the Supremica, with hardware programming. Supremica is a tool that allows to model problems using state machines. It is also possible to simulate and implement all the operations necessary to obtain or synthesize software. Modeling is useful in helping to simplify understanding of the system and solve numerous practical problems, such as problems of industrial control, coordination of multiple equipment in factories, etc. When using modeling, many advantages arise: modularization, that is, being able to look individually at each component and for each requirement; formalization, which allows to obtain a software with guarantees of quality, etc. However, even with multiple features, Supremica, as well as other similar modeling tools, does not export the model to a hardware-compatible programming language. Supremica offers export feature in some formats such as html, dot and among them XML, but not for languages like C, supported by most hardware devices. Therefore, the purpose of this work is to solve this problem by developing an application capable of reading an XML file generated by Supremica and converting it into the programming language, in this case the C. In this way, the hardware can interpret and execute faithfully what was designed, taking to the factory floor the features of a system that was designed with a high level of abstraction and, theoretically, more clearly than usual.